2022
DOI: 10.3390/pharmaceutics14102034
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Analysis of CircRNAs from Plasma Extracellular Vesicle-Enriched Samples for the Detection of Early-Stage Non-Small Cell Lung Cancer

Abstract: Background: The analysis of liquid biopsies brings new opportunities in the precision oncology field. Under this context, extracellular vesicle circular RNAs (EV-circRNAs) have gained interest as biomarkers for lung cancer (LC) detection. However, standardized and robust protocols need to be developed to boost their potential in the clinical setting. Although nCounter has been used for the analysis of other liquid biopsy substrates and biomarkers, it has never been employed for EV-circRNA analysis of LC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…These findings indicate a proinflammatory status induced by SIRT. Immune cell-derived EVs play crucial roles in intercellular communication and regulation of specific mechanisms of both adaptive and innate immune responses [42][43][44]. Similar to our results, previous research by Tung et al demonstrated the influence of EVs on dendritic cell activity and mobility through the study of dendritic cell interaction with exosomes derived from regulatory T cells (Tregs).…”
Section: Discussionsupporting
confidence: 90%
“…These findings indicate a proinflammatory status induced by SIRT. Immune cell-derived EVs play crucial roles in intercellular communication and regulation of specific mechanisms of both adaptive and innate immune responses [42][43][44]. Similar to our results, previous research by Tung et al demonstrated the influence of EVs on dendritic cell activity and mobility through the study of dendritic cell interaction with exosomes derived from regulatory T cells (Tregs).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it would be of benefit to identify differentiating metabolites in tissues through untargeted metabolomics before testing them in the biofluids through targeted metabolomics. Several studies have recently highlighted the role of extracellular vesicles (EVs) and their cargo (protein and RNAs) in lung cancer diagnosis (82)(83)(84)(85), proposing EVs to be another potential source of cancer biomarkers. Therefore, combined metabolomics approaches for EVs phenotyping would provide vital insights into the characteristics of EVs in cancer and potentially identify novel strategies for the early detection of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored the role of circRNAs derived from the lung and carried by EVs [ 100 ], and most of them are focused on their expression and role in lung cancer [ 101 ] ( Table 2 ).…”
Section: Evs In Diagnosismentioning
confidence: 99%
“…A wider analysis of EVs’ composition can support fast stratification and early detection. In this regard, a substantial analysis of EV circRNA signatures can identify lung-cancer-regulated miRNA [ 100 , 102 ]. Furthermore, a proteomic analysis of EV content offers the opportunity to acquire more information about EV biology and identify new biomarkers, contributing to early diagnosis and the design of valid treatments [ 180 ] ( Figure 2 ).…”
Section: Conclusion and Remarksmentioning
confidence: 99%